Kemampuan Mendeklamasikan Puisi Taufik Ismail, Siswa Kelas XII MIPA 1 MAN 1 Kota Makassar - Lidia Lidia; Akmal Hamsa; Kembong Daeng (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This research aims to describe the ability to recite poetry by Taufik Ismail, a class XII student at MAN 1 Makassar City. The research method used is quantitative descriptive. The population in this study was all class XII MAN 1 Makassar City. The sample for this research was 35 people from class XII MIPA 1 using saturation sampling. Data collection techniques used declamation tests and observation sheets. The data analysis technique uses descriptive statistics. The results of this research show that Taufik Ismail's ability to recite poetry was declared capable with the average recapitulation classification score in the range of 70-84, namely 70.34. There were 4 students who got the very capable category with a score of 85-100 (12%), 18 students who got the capable category with a score of 70-84 (51%), 4 people (12%) who got the moderately capable category with a score of 60-69, 4 people (12%), the sample who got the less able category with a score of 50-59, 5 people (14%), and 4 people (11%) who got the less capable category with a score of 0-49. Students who get the very capable category and the capable category are categorized as capable. There were 22 students who received the capable category (63%) and 13 students who received the unable category (37%). So, it can be concluded that the ability to recite the Taufik Ismail poetry of class XII MAN 1 Makassar City students is categorized as capable.